'Call to action' needed for improving perinatal MH programs. Issue 34 (26th August 2022) - Canady, Valerie A.
Abstract : Although intensive perinatal mental health programs have expanded within the U.S. in recent years, too few of these programs serve women with perinatal mood and anxiety disorders (PMADs). Additionally, little is known about the programs, operations and services, the women who are served by them, and the methods of collecting outcome data, researchers stated in an open forum article published in the August issue of Psychiatric Services .